Socialization Prevent of Corruption, Prevention of Narcotics and Free Association in Parsombaan Village, Lubuk Barumun District, Padang Lawas Regency - Erwin Hamonangan Pane (IJCS: International Journal of Community Service, 2022)
Corruption is Becomes real problem serious in Indonesia. Case corruption already no counted again amount. Develop with fast, expanding everywhere, and occur by systematic with advanced engineering and utilise modern technology. Case happening corruption from day day increasingly bloom. Almost every day news about corruption decorate various media. Even Corruption considered normal and understandable so many people Public difficult differentiate name deed corrupt and where actions that are not corrupt. Though already there is commission eradication corruption (KPK) and a number of agency Prevent Corruption other, in fact country this occupy rank top as country the most corrupt in the world.